Efectos De Un Programa De Juegos Predeportivos Para La Velocidad En La Categoria 2005-2006-2007 De La Escuela Deportiva Filandia F.C. (2019)
The present investigation deals with the effects of a program the pre-sports games for speed in children of 10, 11, 12, 13 years of age, whose main objective was to determine the effect that a pre-sports games program has on the development of the speed in ages of children ranging between 10 and 13 years. The methodology used was based on the application of the 35-meter test, which is a test that measures speed as physical capacity. The investigative process was developed with 19 sports children from the filandia FC sports school. With an average of 11.89 years, which was applied to a training program based on the pre-sports games of football based on speed for a total time of 12 weeks. The results obtained in the pretest were 5.81 (sec) and for the posttest it was 5.67 without reaching significant changes (Pvalor = 0.494). The conclusions indicate that a training program to have changes in speed is necessary to take into account the control and management of a more appropriate form of the principles of sports training, as well as more specific exercises focused on the development and improvement of speed that are made and executed during all training sessions.